Socio-Technical Innovation Bundles (STIBs) for Enhancing Women’s Empowerment and Resilience: A Synthesis - Banerjee, Monika; Mukhopadhy, Prama; Chadha, Deepali; Goel, Kritika; Gartaula, Hom N.; Puskur, Ranjitha (CGIAR Initiative on Gender Equality, 2024)
This synthesis report brings together the findings of four case studies carried out by organizations that were brought on board from across India by the International Rice Research Institute (IRRI) as part of the Empower work package of CGIAR’s Gender Equality Initiative (HER+). The focus of the work package is to bundle social and technical innovations for women’s empowerment and resilience. The four case studies highlight projects/programs that combined social, technical, and technological innovations and contributed to increasing women’s empowerment and resilience. The overall objective of this synthesis report is to distill good practices from the findings of these case studies and present them as guidelines for designing socio-technical innovation bundles (STIBs) and scale them up in a context-appropriate manner.